2012
DOI: 10.1117/12.2000627
|View full text |Cite
|
Sign up to set email alerts
|

Indirect photobiomodulation in functional networks

Abstract: Photobiomodulation (PBM) is a non-damaged modulation of laser irradiation or monochromatic light (LI) on a biosystem function. It depends on whether the function is in its function-specific homeostasis (FSH), a negative feedback response for the function to be performed perfectly. Many redundant pathways (RPs) maintain the same cellular function. The full activation of any of RPs can maintain a normal function in its FSH, but partial activation of all the RPs can only maintain a dysfunctional function far from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Neira et al [10] in 2002 reported that low-level laser therapy could release stored fat in adipocytes by the opening of cell membraneassociated pores after a few minutes treatment. Caruso-Davis et al [11] confirmed the finding of Neira et al [10] in the investigation of the efficacy of low-level laser therapy for spot fat reduction and at the same time found that low-level laser irradiation over the waist could significantly reduce waist girth in healthy adults, which is a typical phenomenon of indirect photobiomodulation [12]. Acupoints of St 25 and Sp 15 are located in abdominal area with thicker fat at the level the umbilicus.…”
Section: Discussionmentioning
confidence: 61%
“…Neira et al [10] in 2002 reported that low-level laser therapy could release stored fat in adipocytes by the opening of cell membraneassociated pores after a few minutes treatment. Caruso-Davis et al [11] confirmed the finding of Neira et al [10] in the investigation of the efficacy of low-level laser therapy for spot fat reduction and at the same time found that low-level laser irradiation over the waist could significantly reduce waist girth in healthy adults, which is a typical phenomenon of indirect photobiomodulation [12]. Acupoints of St 25 and Sp 15 are located in abdominal area with thicker fat at the level the umbilicus.…”
Section: Discussionmentioning
confidence: 61%
“…iPBM might be mediated by redundant pathways because successful ordinary stress is mediated by redundant pathways. In our C2C12 studies [13], The Fmax of C2C12 myoblasts in normal glucose is the normal proliferation, and its FmaxSH is nPlSH. We found that RLED at 640 nm promoted the normal proliferation of C2C12 myoblasts from 4 days on and IGF-1/FOXO3a (forkhead box O family 3a) was completely activated/inhibited.…”
Section: Indirect Photobiomodulationmentioning
confidence: 84%
“…Youk International Journal of Photoenergy found the growth rate peaked in glucose between 0.06% and 0.20%, which corresponded to the normal growth that resists the concentration change of glucose between 0.06% and 0.20% [10]. We also have found that these are the best concentrations of glucose, normal glucose, in which C2C12 cells proliferated in their optimal rate and between which there was no significant difference of the proliferation rate, and the low/high glucose whose concentration was lower/higher than the one of normal glucose, and in which the C2C12 cells proliferated in a rate lower than the optimal rate [11][12][13]. In other words, the C2C12 cell proliferation in normal glucose was a normal proliferation which resisted the concentration change in the normal glucose.…”
Section: Function-specific Homeostasismentioning
confidence: 99%
“…1 Tumor growth is always normal. It is maintained by tumor growthessential/nonessential subfunctions.…”
mentioning
confidence: 99%